Specific heat study of magnetic excitations in a one-dimensional S =1 Heisenberg magnet with strong planar anisotropy: Сильно коррелированные системы и высокотемпературная сверхпроводимость - Feher, A.; Orendáč, M.; Orendáčová, A.; Čižmár, E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
The results of experimental studies of the specific heat of the magnetic chain compounds Ni(C2H8N2)2Ni(CN)4, Ni(C11H10N2O)2Ni(CN)4, and Ni(C10H8N2)2Ni(CN)4×H2O are reported. All compounds are identified as S = 1 planar Heisenberg magnetic chains with large planar anisotropy and different values of the in-plane anisotropy constant. The low-temperature specific heat data are interpreted assuming the existence of noninteracting excitons and antiexcitons as elementary excitations from the singlet-ground state. The extendedstrong-coupling model is used for analysis of the data at higher temperatures. The applicability of the models used with respect to the value of the in-plane anisotropy is discussed.